Kangaroo Mother Care for Low Birth Weight Babies: A prospective Observational Study - Subedi, K; Aryal, DR; Gurubacharya, SM (Journal of Nepal Paediatric Society, 2009)
Introduction: Kangaroo Mother Care is the low cost, humane technique for caring low birth weight babies by direct skin to contact with the mother. Objective: The Prospective observational study was done to see the effect of KMC especially on weight gain on low birth weight babies weighing 2000 grams or less at Special Care Baby Unit of Paropakar Maternity and Women's hospital, Kathmandu. Method: The study was conducted in Special Care Baby Unit (SCBU) of Paropakar Maternity and Women's Hospital over 7 months period May 2007 to Nov. 2008 (from Baishakh 2064 to Kartik 2065). The method of care consisted of skin to skin contact between the mother and the infant. Result: It was observed that babies had good weight gain of average 30gms/day and had short duration of hospital stay of average 9 days. Babies had less morbidities like hypothermia, apnea, skin infections and oral thrush. 100% babies had exclusive breast feeding and KMC was acceptable to mothers. Conclusion: Kangaroo Mother Care shows early and good weight gain in low birth weight babies. It is simple, low cost technique and well acceptable by mother and family and can be continued at home. Key words: Kangaroo mother doi:10.3126/jnps.v29i1.1593 J. Nepal Paediatr. Soc. Vol.29(1) p.6-9